The 13th international. congress on autoimmunity 2022 (AUTO13) Athens: An event as big as the topics - Etsatti, Abdutrahman; Atwani, Abdutkarim; Seida, İsa; Atrais, Mahmoud; Seida, Ravend; Esirgun, Sevvat Nit; Abalı, Tunahan; Kıyak, Zeynep; Mahroum, Naim (Israel Medical Association Journal, 2022)
The gathering of the 13th International Congress on Autoimmunity 2022 (AUTO13) could not have been held at a place better than the beautiful city of Athens, Greece, at the Megaron Athens International Conference Center (MAICC), which is short distance from the Acropolis. With thousands of participants from more than 70 countries and five continents, the in-person meeting of AUTO13 was a huge success.
Keywords: Autoimmunity; Autoantibodies; Autoimmune/Inflammatory Syndrome Induced by Adjuvant (ASIA); Coronavirus Disease 2019 (COVID-19); post-COVID